Comprehension as a Component of the Future Leader’s Professional Competence in the Field of Innovative Management of Educational Institution (as Far as the Leaders` Activity at Educational Institutions of the Carpathians) - Sas, Natalia (Journal of Vasyl Stefanyk Precarpathian National University, 2014)
The author analyses philosophical, linguistic, psychological, sociological and management approaches to the content of comprehension and peculiarities of comprehension as a constituent of the future leader`s professional competence in the innovative management of the educational institution. The problem under consideration is sure to be relevant due to the question elaboration connected with the implementation of the innovative management means the exact awareness of the specific character of practical application of the new management forms at the educational institution. The question of general terms is a constituent of the problem of comprehension. According to the national Frame of skills competence is a person`s ability to perform particular kind of activity via knowledge, comprehension, skills, values and other personal qualities. In other words it is a dynamic combination of knowledge, comprehension, skills, values and other personal qualities. From this it can be concluded that comprehension alongside knowledge, skills and values is the component of innovative management competence. Psychology treats comprehension as a complex analytic-synthatic mental activity which tends to reveal and realise the inner essence of the objects, processes and phenomena as well as links, relations, and dependence reflected in it. In the innovative management of educational institutions management decisions and problem solving activity, setting new objectives, tasks and methods presuppose the necessity for changing the leader`s way of thinking. The subject of comprehensive sociology is adeliberateaction, connected with the subjective predictable sense. The development of the innovative e management competence is determined by the appropriate realization of all the aspects of the professional management. The Carpathians are famous for natural, ecological, technical, organizational, economic, social, cultural and ethnic peculiarities. The specific ones are those which should be realized and taken into consideration by the leaders of educational institutions in the Carpathians: their being densely populated, the distance between the places of residence and schools, household, unique ethnic and handicraft traditions.